Analysis of the influence of organizational career management and individual career mangement on career effectiveness health functional positions - Meilia Chaidzah Rustiana; Sebastiana Viphindrartin; Aris Prasetyo (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Managing employees is a management job that is quite complicated because it involves several practices and policies in which there must be compatibility between the organizational strategies that are expected by employees, especially in terms of employee careers. Career management carried out by an organization will create employee perceptions that the organization is committed to career development so that it will affect the effectiveness of employee careers. The purpose of this study was to analyze the effect of organizational career management and individual career management on career effectiveness in functional health positions. This research was an observational analytic study and used a cross sectional research design. The population in this research was all employees of executive positions who have the potential to occupy functional positions, totaling 40 people. The results showed that Organizational career management and individual career management for Functional Position employees at the Situbondo District Health Office are in the good category . Test results using SMART PLS show that there is a positive relationship between organizational career management and individual career management on career effectiveness in functional health positions. Abstrak: Mengelola pegawai merupakan pekerjaan manajemen yang cukup rumit karena melibatan beberapa praktik dan kebijakan yang didalamnya harus tetap ada kesesuaian antara strategi organisasi yang diharapkan karyawan khususnya dalam hal karir pegawai. Manejemen karir yang dilakukan oleh suatu organisasi akan menciptakan persepsi pegawai bahwa organisasi memiliki komitmen pada pengembangan karir sehingga akan mempengaruhi efektivitas karir pegawai. Tujuan penelitian ini adalah untuk menganalisis pengaruh manajemen karir organisasional dan manajemen karir individu terhadap efektivitas karir pada jabatan fungsional kesehatan. Jenis penelitian ini yaitu analitik observasional dengan menggunakan desain penelitian cross sectional. Populasi penelitian ini yaitu seluruh pegawai jabatan pelaksana yang memiliki potensi menduduki jabatan fungsional yang berjumlah 40 orang. Hasil penelitian menunjukkan bahwa Manajemen karir organisasional dan manajemen karir individu pada pegawai Jabatan Fungsional di Dinas Kesehatan Kabupaten Situbondo berada di interpretasi kategori baik. Hasil uji dengan menggunakan SMART PLS menunjukkan bahwa terdapat hubungan yang positif antara manajemen karir organisasional dan manajemen karir individu terhadap efektivitas karir pada jabatan fungsional kesehatan.